On the importance, vastness and limits of Physiology - Delgado, Honorio F. (1920)
I think it's not here, not now, where and when should develop guidelines ideas in the teaching of physiology, nor the detailed rationale for the organization and content of the program of teaching the course. Although other is the chance of exposure of the pedagogical approach and scientific appreciation of the discipline teaching, I would like to express my view and solve two problems that arise in developing the program and general human physiology here. The first problem to which I refer is on the extension of the course. Medicine today is essentially physiological; dynamic agency approach has completely revamped the way we think and address the issues of pathology and therapeutics. So profound is the influence of the new point of view, that even the leaves and Anatomy from static to turn physiologic. One of these aberrations, so frequent in the history of scientific thought, made long medicine based its guidance on concepts detached studio's corpse the living individual. What should have been simply and solely a junior middle knowledge, became, in a sense, in idea or better say in guiding the medical judgment of yesteryear.